Two-Dimensional Physical Simulation of the Seepage Law of Microbial Flooding - Yongheng Zhao; Jianlong Xiu; Lixin Huang; Lina Yi; Yuandong Ma (Energies)
The study of seepage laws during microbial enhanced oil recovery helps to elucidate the mechanisms behind microbial flooding, and the use of large-scale physical simulation experimental devices can more objectively and accurately investigate the seepage laws of microbes in porous media, and evaluate the oil displacement efficiency of microbial systems. In this study, physical simulation experiments of microbial flooding were conducted via a slab outcrop core, and the biochemical parameters such as the concentration of Bacillus subtilis, nutrient concentration, surface tension, and displacement pressure data were tracked and evaluated. The analysis revealed that the characteristics of the pressure field change during microbial flooding and elucidates the migration rules of microbes and nutrients, as well as the change rule of surface tension. The results show that after the microbial system is injected, cells and nutrients are preferentially distributed near the injection well and along the main flow paths, with the bacterial adsorption and retention capacity being greater than those of the nutrient agents. Owing to the action of microorganisms and their metabolites, the overall pressure within the model increased, From the injection well to the production well, the pressure in the model decreases stepwise, and the high-pressure gradient zone is mainly concentrated near the injection well. The fermentation mixture of Bacillus subtilis increased the injection pressure by 0.73 MPa, reduced the surface tension by up to 49.8%, and increased the oil recovery rate by 6.5%.